THE REPRESENTATION OF A POLYNESIAN THROUGH QUEQEEQ CHARACTER IN HERMAN MELVILLE’S MOBY DICK - Ambar Andayani; Jupriono Jupriono (Anaphora : Journal of Language, Literary, and Cultural Studies, 2019)
This research applies a literary anthropology approach that focuses the study on the uniqueness of Queqeeq character represented in Moby Dick (Mellvill, 1962). That uniqueness contains physical characteristics as a Polynesian, cultural behavior, belief, and dialect. Queqeeq character is described as a very sober man, consistent in his words and manners, and referring to Polynesid race, with large black eyes, natural dark skin, and unworldly tattoos. Quegeeq is represented as a character of a hard worker, agile, and tough as a seaman in the Pacific ocean. In religion, Queqeeq is described as a primitive ritual-religion person, who is serious in fasting; not to eat and talk in the Ramadan time, prays ritually through a wooden idol, following the ritual-religion custom of Polynesian. Generally, it can be concluded that Melville in Moby Dick (1962) succeeds in representing the specific characteristics of Polynesian culture through character and characterization of Queqeeq